2022
DOI: 10.1039/d2ob00553k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cholinesterase inhibitory activity study of Amaryllidaceae alkaloid analogues with N-methyl substitution

Abstract: Polycyclic compounds with N methyl substitution, structurally related to Amaryllidaceae alkaloids, have been synthesised, together with their analogues bearing a quaternary nitrogen atom. To prevent the lone electron pair of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Furthermore, several crucial interactions also have been reported in numerous studies over the past 5 years. Particularly, the pi‐pi shape interactions with TRP279, TRP84, and PHE330, as well as hydrogen bonding with PHE288 and ARG289, have been highlighted (Jansa et al., 2022; Qi et al., 2023; Zahedi et al., 2023). However, none of the active compounds obtained from the in vitro study were found to fit within the active site using either standard or extra precision methods.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several crucial interactions also have been reported in numerous studies over the past 5 years. Particularly, the pi‐pi shape interactions with TRP279, TRP84, and PHE330, as well as hydrogen bonding with PHE288 and ARG289, have been highlighted (Jansa et al., 2022; Qi et al., 2023; Zahedi et al., 2023). However, none of the active compounds obtained from the in vitro study were found to fit within the active site using either standard or extra precision methods.…”
Section: Resultsmentioning
confidence: 99%
“…Its hydroxyl immediately attacked the ketone group and formed a very stable hemiacetal 5 that resisted further reduction (Scheme 3). Product 5 was then subjected to the Boc cleavage with ZnBr 2 and methylation using our previously optimised method, [22] which resulted in a moderate yield of a five‐membered tazettine analogue 6 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2022, polycyclic compounds bearing N-methyl substitution were generated using Boc as the protected group with excellent enantiomeric excess by Matousova group (Scheme 40). [65] In 2016, Hodgson group reported a β-iodo Morita-Baylis-Hillman reaction to synthesize (Z)-iodo ester, followed by Sonogashira cross-coupling-5-exo-dig lactonization to produce (Z)-γ-alkylidenebutenolide (Scheme 41a). [66] In the following year, the same group expanded the scope of the reaction (Scheme 41b).…”
Section: Reaction With Alkynementioning
confidence: 99%
“…In 2022, polycyclic compounds bearing N‐methyl substitution were generated using Boc as the protected group with excellent enantiomeric excess by Matousova group (Scheme 40). [65] …”
Section: Reaction With Alkynementioning
confidence: 99%